Analysis of Consumer Protection in the Insurance Claim Process Based on Law No. 8 of 1999 on Consumer Protection - Silvana Nur Rahmat Lukum; Weny Almoravid Dungga; Suwitno Yutye Imran (International Journal of Law, Crime and Justice, 2025)
This study aims to analyze the legal protection for insurance customers in the settlement of policy claims at PT Asuransi Bumi Putera, with reference to Law No. 8 of 1999 concerning Consumer Protection. The main problem faced by customers is the delay in payment of claims, which is contrary to the main purpose of insurance to compensate for losses experienced by customers. Based on available data, many claims have not been paid, indicating the non-compliance of insurance companies with their obligations. This research examines the forms of legal protection regulated in the Consumer Protection Law, particularly regarding the customer's right to obtain clear information, compensation, and dispute resolution. In addition, this study also highlights the preventive and repressive aspects of legal protection, where preventive protection aims to prevent disputes from occurring, while repressive protection provides legal avenues for aggrieved customers to obtain compensation. While the law has provided a clear basis of protection, consistent implementation and enforcement are still needed to ensure customer rights are fulfilled. This research is expected to contribute to improving legal protection for insurance customers in Indonesia, as well as encouraging insurance companies to fulfill their obligations in a timely manner in accordance with applicable regulations.